The impact of organizational culture on the performance of human resources - AOUFI, Mustapha; HAMOUD, Nacer (Social Sciences Journal)
This study was an attempt to identify the organizational culture prevailing within the Algerian organization, the most important characteristics and the exent of thier impact in the performance of human resources’s level , the researcher has used a descriptive and analytical approach which has based on the questionnaire as a key tool for gathering information and data while the use of sample search method and the application of appropriate statistical tools to the nature of the search as a mean , standard deviation and correlation coefficiens (Alpha Cronbach , Pearson and Spearman ) and which has carried out of using statistical program(spss).